Analisis Psikologi Komunikasi Dalam Praktik Haṭha Yoga - Ni Ketut Anjani, Ni Ketut Anjani (Jurnal Yoga dan Kesehatan, 2026)
Communication psychology in hatha yoga practice plays a strategic role in supporting mental health improvement through internal and external communication processes. This study aims to analyze how communication dynamics in hatha yoga practice contribute to mental health. This study used a qualitative approach with a literature review method that analyzed approximately 18 scientific sources in the form of journal articles, textbooks, and classic yoga manuscripts. The results show that hatha yoga practice is not only a physical activity, but also a psychological communication process involving intrapersonal and interpersonal communication that plays a role in the formation of self-awareness and emotional regulation. Internal communication occurs through awareness of the breath, body, and mind, while external communication is reflected in the interaction between instructors and participants. This process contributes to emotional regulation, stress management, and increased self-awareness. The novelty of this study lies in the integration of communication psychology perspectives into the study of yoga, which confirms that the effectiveness of hatha yoga is greatly influenced by the quality of communication during the practice.